The Scholar as Human Research and Teaching for Public Impact - Bartel, Anna Sims; Castillo, Debra A. (Publicly Engaged Scholars: Identities, Purposes, Practices, 2022)
The Scholar as Human brings together faculty from a wide range of disciplines-history; art; Africana, American, and Latinx studies; literature, law, performance and media arts, development sociology, anthropology, and Science and Technology Studies-to focus on how scholarship is informed, enlivened, deepened, and made more meaningful by each scholar's sense of identity, purpose, and place in the world. Designed to help model new paths for publicly-engaged humanities, the contributions to this groundbreaking volume are guided by one overarching question: How can scholars practice a more human scholarship? Recognizing that colleges and universities must be more responsive to the needs of both their students and surrounding communities, the essays in The Scholar as Human carve out new space for public scholars and practitioners whose rigor and passion are equally important forces in their work. Challenging the approach to research and teaching of earlier generations that valorized disinterestedness, each contributor here demonstrates how they have energized their own scholarship and its reception among their students and in the wider world through a deeper engagement with their own life stories and humanity. Contributors: Anna Sims Bartel, Debra A. Castillo, Ella Diaz, Carolina Osorio Gil, Christine Henseler, Caitlin Kane, Shawn McDaniel, A. T. Miller, Scott J. Peters, Bobby J. Smith II, José Ragas, Riché Richardson, Gerald Torres, Matthew Velasco, Sara Warner Thanks to generous funding from Cornell University, the ebook editions of this book are available as Open Access volumes from Cornell Open (cornellpress.cornell.edu/cornell-open) and other repositories.